Assessment of the factors affecting the provision of a patient counseling service in independent community pharmacies in Manila - Docena, Alison Mary A.​; Luceñara, Melissa L.​; Tan, Mara Lois V.​
Researches show that patient counseling and education promotes medication adherence, rational use of medicines, understanding of health, and allows the patient to get the most out of their health care. Patient counseling, however, is not widely practiced in the Philippines and studies regarding it are lacking. This study aims to individually assess the factors that contribute to the provision of patient counseling service in independent community pharmacies in Manila A questionnaire was given to pharmacists of DSAP-member pharmacies in Manila. Regression analysis of the factors and correlation of the factors to the patient demographics were used to assess the factors. Among the respondents. 91.30% offer patient counseling. Participants were mostly female 50-57 years old, and have had 20 or more years of service. Pharmacist accessibility, patient interest, pharmacist knowledge, and support from other healthcare professionals are the most important factors in the pharmacy environment, patient-related, pharmacist-related, and health system categories, respectively. The top three factors determined by pharmacists were privacy and/or designated space, the patient?s time, and the patient's interest in patient counseling. A weak positive correlation was observed (1) between age to the accessibility and training of pharmacists and (2) between years of service to the belief that the physician?s information is enough.